Trend and Correlation Between the Scope of Tuberculosis Preventive Therapy (TPT) and Treatment Success Rate (TSR) with the Case Notification Rate (CNR) of Tuberculosis in Indonesia During 2021-2023 - Nur Baiti; Chatarina Umbul Wahjuni; Kurnia Dwi Artanti (Media Gizi Kesmas, 2025)
Background: Tuberculosis remains a major public health problem in Indonesian. The Indonesian TB control program for the 2020–2024 period aims to accelerate the achievement of national TB elimination by 2030 and contribute to ending the global TB epidemic by 2050, aligning with the WHO's End TB Strategy. As part of this national strategy, the government has implemented various interventions, including the provision of Tuberculosis Preventive Therapy (TPT) to high-risk groups and improvements in the Treatment Success Rate (TSR). Objectives: This research aims to analyze the trends and the correlation between TPT and TSR with the incidence of tuberculosis, measured through the Case Notification Rate (CNR) at the provincial level during 2021-2023. Methods: This research is an ecological study using quantitative methods. The data in this research are based on tuberculosis prevention reports from the Directorate of Disease Prevention and Control, Ministry of Health of Indonesia, from 2021 to 2023. The variables analyzed in this research are TPT coverage and TSR with CNR in 2021-2023. Results: The study results show an increasing trend in CNR in Indonesian provinces for three consecutive years. Furthermore, TPT coverage has also increased, although it remains relatively low, and TSR shows variation across provinces. Spearman's analysis indicates a correlation between TPT, TSR, and CNR. However, the correlations are weak and mostly negative. Conclusion: TPT coverage and TSR in Indonesia showed improvement during 2021–2023, although disparities remained between provinces. The weak correlations between TPT, TSR, and incidence rates indicate that prevention and treatment interventions have not yet fully impacted the reduction of new cases. Strengthening case detection, enhancing contact tracing, and expanding TPT are needed to accelerate the decline in TB incidence nationally.